Ambientes formales para el logro de aprendizajes deseables en los estudiantes de básica superior de la Unidad Educativa José Ángel Palacio, período 2023- 2024 - Jirón Álvarez, Byron René (2024)
The present work, which deals with Formal environments for the achievement of desirable learning in upper elementary students of the José Ángel Palacio Educational Unit, period 2023- 2024, was developed and worked with the following general objective: to determine the incidence of formal environments within the educational practice for the achievement of learning in upper elementary students of the José Ángel Palacio Educational Unit, period 2023- 2024. For this purpose, the following methods were used: scientific, observational, descriptive, analytical and statistical, each of which helped to elucidate the postulates of the theoretical framework, in order to strengthen the research work. Likewise, a representative sample of 92 human talents distributed in 81 students and 11 teachers was taken as a reference, to which an interview to the teachers and a survey to the students were applied. Several deficiencies in the teaching environments were determined, which can be improved through configurations of desirable learning environments, since in the face of the realities determined in the classroom there are strategies that contribute to counteract the needs that the student has in his learning and that are directly related to the place where the teaching-learning process takes place. To this end, the alternative guideline "Formal environments in the improvement of desirable learning" was designed with the purpose of contributing to the formation of suitable, participatory and innovative environments in the classroom where learning is not only focused on the acquisition of knowledge, but also transcends towards the development of practical skills, critical thinking, problem solving and even the acquisition of socioemotional skills.